Analisis Butir Soal Tipe Multiple Choice Questions pada Penilaian Harian Sekolah Dasar - Wandri Ramadhan; Fildza Malahati; Kharisma Romadhon; Syahrul Ramadhan (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2023)
Daily assessment is an important educational instrument because it can assist teachers in measuring student learning progress. One of the most commonly used types of evaluation is Multiple Choice Questions (MCQs). This study aims to reveal the quality of daily assessment items in the form of MCQs based on effectiveness, reliability coefficient, and item deception. This quantitative descriptive research uses statistical data analysis, which is then processed into a description. The assessment instrument grid used theme 4 elementary school material. The instrument was tested on 20 class V MIN 3 Padang students. The results of this study found that the items in the test instrument were good enough to use because they had an average score of 11,367, a moderate difficulty level with a score of 0.568, and element values were quite reliable. They had good discriminating power with a score of 0.070. Even so, there are still a number of items that are not of high quality in terms of difficulty level, discriminating power, and question distraction, so they need to be revised or replaced with other items.